Revision der paläarktischen Arten von Phytosciara Frey (Diptera: Sciaridae). - Mohrig, Werner; Menzel, Frank (Contributions to Entomology = Beiträge zur Entomologie, 1994)
The 28 Palaearctic species of Phytosciara are considered to be a monophyletic, belonging to the subgenera Phytosciara s. str. (4 species), Dolichosciara (11 species) and Prosciara (12 species). Phytosciara breviantennata (Mohrig & Mamaev) was unplaced until now. Five species (Ph. nepalensis spec. nov., Ph. oldenbergi spec. nov., Ph. subflavipes spec. nov., Ph. subornata spec. nov., Ph. subungulata spec. nov.) are described as new and 10 new combinations and 1 new synonyms are given. Keys to species and their habitats and distribution are discussed Phytosciara coheri spec. nov., from Thailand is described and the types of Sciara nigra Wiedemann and Psilomegalosphys xanthogaster Enderlein are revised.Nomenclatural Actsmagnifica (Mohrig & Menzel, 1994) (Bradysia), nom. n.; comb. n. pro Phytosciara (Phytosciara) melanura Mohrig & Krivosheina, 1983, nec Mohrig & Mamaev, 1982neofusca (Mohrig & Krivosheina, 1982) (Bradysia), comb. n. hitherto Phytosciara neofuscazingiberis (Sasakawa, 1985) (Bradysia), comb. n. hitherto Phytosciara zingiberisnodulosa (Mohrig & Krivosheina, 1985) (Lycoriella (Hemineurina)), comb. n. hitherto Phytosciara (Phytosciara) nodulosabreviantennata (Mohrig & Mamaev, 1983) (Phytosciara), comb. n. hitherto Corynoptera breviantennataflavipes (Meigen, 1804) (Phytosciara (Dolichosciara)), Lectotype described as Sciara flavipesnepalensis Mohrig & Menzel, 1994 (Phytosciara (Dolichosciara)), spec. n.subflavipes Mohrig & Menzel, 1994 (Phytosciara (Dolichosciara)), spec. n.subornata Mohrig & Menzel, 1994 (Phytosciara (Dolichosciara)), spec. n.halterata (Lengersdorf, 1926) (Phytosciara (Phytosciara)), Lectotype described as Sciara halteratamacrotricha (Lengersdorf, 1926) (Phytosciara (Phytosciara)), Lectotype described as Psilomegalosphys macrotrichaoldenbergi Mohrig & Menzel, 1994 (Phytosciara (Phytosciara)), spec. n.coheri Mohrig & Menzel, 1994 (Phytosciara (Prosciara)), spec. n.filichaeta (Hippa & Vilkamaa, 1991) (Phytosciara (Prosciara)), comb. n. described as Prosciara filichaetalobata Antonova, 1977 (Phytosciara (Prosciara)), syn. n. of Phytosciara (Prosciara) ussuriensis Antonova, 1977pectinifera (Hippa & Vilkamaa, 1991) (Phytosciara (Prosciara)), comb. n. described as Prosciara pectiniferapentacanta (Hippa & Vilkamaa, 1991) (Phytosciara (Prosciara)), comb. n. described as Prosciara pentacantaplusiochaeta Hippa & Vilkamaa, 1991 (Phytosciara (Prosciara)), comb. n. hitherto Prosciara plusiochaetaporrecta (Lengersdorf, 1929) (Phytosciara (Prosciara)), Lectotype described as Sciara (Neosciara) porrectaprosciaroides (Tuomikoski, 1960) (Phytosciara (Prosciara)), comb. n. described as Bradysia prosciaroidessubungulata Mohrig & Menzel, 1994 (Phytosciara (Prosciara)), spec. n.ungulata (Winnertz, 1867) (Phytosciara (Prosciara)), Lectotype described as Sciara ungulataxanthogaster Enderlein, 1911 (Psilomegalosphys), LectotypePhorodonta Coquillet, 1910 (Sciaridae), nom. n. for Odontonyx Rübsaamen, 1894, nec Stephens, 1828